The Neurospora crassa colonial temperature sensitive 2, 4 and 5 (cot-2, cot-4 and cot-5) genes encode regulatory and structural proteins required for hyphal elongation and branching - Zipi Resheat-Eini; Alex Zelter; Rena Gorovits; Nick D. Read; Oded Yarden (Fungal Genetics Reports, 2008)
The morphology and the genetic defects of theNeurospora crassa colonial temperature-sensitive-2, -4 and -5 mutants were analyzed. cot-2 is allelic to gs-1 and encodes a component of the glucan synthesis process. cot-4 encodes the catalytic subunit of a type 2B phosphatase and is allelic to calcineurin (cna-1). cot-5 encodes a homologue of the S. cerevisiae ALG2 manosyltransferase-encoding gene, a component of the dolichol pathway.